Questioning Invisibility. - Buechley, Leah (Computer (00189162), 2010)
In this article, the author reflects on invisibility in computing. He wonders if invisibility is always a good thing or if it should be a guiding design for ubiquitous computing. He relates the instances where the invisibility of technology breaks down and how it can cause not only inconvenience and frustration but also reveal the inelegance and fragility of the technology. He believes that invisibility is a narrow design goal and does not capture the full range of technological or creative possibilities.